UPAYA MENINGKATKAN KEMAMPUAN MENULIS UNSUR INTRINSIK HIKAYAT DENGAN MENGGUNAKAN METODE COOPERATIVE SCRIPT DI KELAS X SMK - Neng Nani Aini; Nelly Aprianti; Yusep Ahmadi F (IKIP Siliwangi, 2019)
This research is motivated by the observations of researchers that the ability to write intrinsic elements of the saga is very low. This was allegedly due to the application of inappropriate learning methods. Then the interests and motivation of student learning are also very lacking so students cannot play an active role. The purpose of the formulation of this problem is to describe and know the planning of writing intrinsic elements of saga, the results of Cooperative Script learning on the ability to understand the intrinsic elements of class X students' stories. The research method used is quantitative experimental methods. The design of this research method is the type of design of One Group Pretest-Posttest Design. The population studied were all SMK students with a total of 60 people. While for the sample, there are 20 class X students. Data collection techniques are through research tests/questionnaires. Data processing techniques are carried out using statistics. The results of this study are that there is an increase in understanding of saga learning. Students are able to write intrinsic elements of the story well and students can feel the results of learning are very satisfying. Obtained an increase in the results of learning using the Cooperative Script method there are significant differences in values, the highest value of the initial test of 78 and the final test value of 90, it was concluded that this method is suitably applied to learning writing.